Exploring engineering students’ perception on the effectiveness of community projects - Boon, Yih Mah; Farhana Shukor; Ahmad Zia Ul-Saufie (Penerbit Universiti Kebangsaan Malaysia, 2023)
In this endemic phase, it is more common to have more online classes as students and advisors worldwide are more prone to choose several technology aids to teach and learn at Higher Education institutions. In this study, Entrepreneurially Minded Learning through university-community engagement in Engineering education worked as the base for students to prepare in an English course for completing their community projects. This study investigated the perceptions of 24 second-semester foundation students in applying engineering knowledge. Consultation with their advisors about their plans is crucial for students to execute their projects throughout the 12 weeks of the semester. In this study, a working methodology on community project execution involved Phase 1 (Planning and Design), Phase 2 (Analysis, Monitoring, and Delivery), and Phase 3 (Evaluation). Semi-structured interview sessions elicit responses from the students. The benefits of community projects are an increased sense of social responsibility, awareness of future avenues, more recent platforms fully utilised for documentation purposes, and increased engagement. The challenges include the limitation to conducting community projects online, lack of skills in working in online groups, and low community engagement. Students' engagement with the community via community projects will assist them in applying their academic knowledge to solving challenges from the actual world. Students needed support from the advisors to complete the task assigned successfully to nurture their skills to apply knowledge gained from their community projects at their future workplaces.